2022
DOI: 10.3390/nu14214444
|View full text |Cite
|
Sign up to set email alerts
|

Free Sugar Intake and Periodontal Diseases: A Systematic Review

Abstract: High free sugar intake is associated with an increased risk of various non-communicable diseases. We aimed to systematically review articles investigating the association between free sugar intake and periodontal diseases. This systematic review was conducted according to PRISMA guidelines and was registered in the PROSPERO database (CRD42022337828). We obtained articles from PubMed, Web of Science, and Scopus in April 2022. The study selection was performed according to predefined eligibility criteria based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…High sugar intake is associated with dyslipidemia and can also influence the development of gum disease. Diets high in sugar have been shown to increase cholesterol levels and contribute to gum inflammation and disease progression [ 25 ]. The dietary intake of cholesterol could impact both cholesterol levels in the body and the risk of gum disease.…”
Section: Methodsmentioning
confidence: 99%
“…High sugar intake is associated with dyslipidemia and can also influence the development of gum disease. Diets high in sugar have been shown to increase cholesterol levels and contribute to gum inflammation and disease progression [ 25 ]. The dietary intake of cholesterol could impact both cholesterol levels in the body and the risk of gum disease.…”
Section: Methodsmentioning
confidence: 99%
“…Regular consumption of these drinks has been associated with increased biomarkers of inflammation [ 69 , 70 , 71 , 72 , 73 ] and has been studied in association with a variety of diseases [ 74 , 75 , 76 , 77 , 78 ]. Sugar sweetened carbonated drinks, which often are consumed between meals without rinsing or tooth brushing afterwards, have been associated with increased risk of periodontal disease [ 79 , 80 , 81 , 82 ] as well as dental caries and tooth erosion [ 83 , 84 , 85 , 86 ]. The consumption of processed meat, fried foods, and sugar sweetened carbonated drinks is very common in the Western diet [ 60 ] that is highly prevalent in Germany [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a sugar-rich diet escalates the risk of developing periodontal disease in both teenagers [13,27] and children [28]. An elevated sugar intake perpetuates a prolonged hyperglycemic state, escalating systemic inflammation and the susceptibility to periodontal disease [29]. Moreover, sugar consumption can alter the diversity of the oral microbiome and contribute to the development of periodontal pathogens [29].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated sugar intake perpetuates a prolonged hyperglycemic state, escalating systemic inflammation and the susceptibility to periodontal disease [29]. Moreover, sugar consumption can alter the diversity of the oral microbiome and contribute to the development of periodontal pathogens [29]. It is widely observed that children and adolescents globally surpass current recommendations in sugar consumption [30].…”
Section: Discussionmentioning
confidence: 99%